STUDENTS’ ATTITUDE TOWARD PE LESSONS ACCORDING TO SELF-PERCEIVED PHYSICAL FITNESS (Fiep Bulletin - online, 2014)
The main aim of our paper is to describe the attitude of pupils to physical education (PE) regarding their gender and selfperceived physical fitness (SPF). We conducted the survey in 2012 during the teaching practice of PE student teachers and we used the questionnaire “Diagnostics of PE lesson for pupils” to collect relevant data. Altogether 1,537 questionnaires (711 from girls and 826 from boys attending secondary and high schools) were analyzed. Regarding the content, PE lessons with games prevailed (35% of them – basketball). In boys, statistically significant differences were found in four scales, an additional scale and in total evaluation between the upper and lower halves of classes in terms of SPF. There was found no significant difference for girls. Regarding the analysis of the relationship to PE in terms of popularity, in both genders a significantly positive relationship toward realized PE lesson was found by a group that likes PE. To conclude, SPF is not reflected in the pupil’s relationship toward PE lessons, but the popularity of PE has a positive association with the evaluation of PE lessons. Acknowledgment: This paper was supported by the ECO P project „Strengthening scientific potential of the research teams in promoting physical activity at Palacky University” (reg. No. CZ.1.07/2.3.00/20.0171) and by the Faculty project „Association between selfperceived physical fitness of pupils and their attitude to Physical Education lessons: Use of pedometers” (FTK :2013:010).
Keywords: Questionnaire; popularity of PE; gender; physical fitness; relationship